Rekonstruksi Model Integratif Epistemologi Pendidikan Islam melalui Perbandingan Perspektif Klasik–Modern: A Systematic Literature Review - Yusuf Efendi; Aljamaedi Aljamaedi; Deby Habja Musdalifa; Riki Saputra; Sukmareni Sukmareni (CV. Bimbingan Belajar Assyfa, 2026)
This study aims to reconstruct an integrative model of Islamic educational epistemology through a comparison of classical and modern perspectives based on a synthesis of scholarly literature. The study employed a Systematic Literature Review (SLR) method by analyzing 30 journal articles addressing Islamic educational philosophy, epistemology, knowledge integration, character education, digital transformation, and contemporary scientific developments in Islamic education. The analysis was conducted through stages of article identification, data extraction, thematic classification, comparative analysis, and conceptual synthesis. The findings reveal that classical Islamic educational epistemology emphasizes revelation (naql), reason (‘aql), adab, and character formation, while the modern perspective retains these foundations while incorporating contextualization, empirical experience (tajribah), knowledge integration, and openness to scientific and technological advancement. The study also identifies a strong tendency toward an integrative paradigm that connects multiple sources of knowledge within a holistic educational framework. Based on the literature synthesis, this research proposes an integrative model of Islamic educational epistemology consisting of five key components: naql, ‘aql, tajribah, adab, and contemporary science and technology. This model provides a conceptual foundation for developing Islamic education that is responsive to the challenges of the twenty-first century